Supplementation with serine-enriched non-essential amino acids from minimum essential medium promotes blastocyst development of in vitro-fertilized bovine embryos - Nobuhiko ITAMI; Yuji HIRAO (The Journal of Reproduction and Development)
To produce an embryo, a high conception rate must be complied along with four evaluation criteria based on the timing of early cleavage and proper embryo morphology (hereafter, these blastocysts will be referred to as “four-criteria-compliant blastocysts”). Therefore, it is necessary to construct a culture system for high efficiency production of embryos meeting these four criteria. Non-essential amino acids (NEAAs) are widely used for the culture of bovine embryos fertilized in vitro; however, the necessity and optimal concentration of individual NEAA must be verified to produce four-criteria-compliant blastocysts. DNA methylation is a critical event for blastocyst formation in bovines, and serine is a common NEAA that serves as a methyl donor and participates in DNA methylation. Serine is generally added at a concentration of 100 µM in bovine embryo culture medium. However, the rate of formation of four-criteria-compliant blastocysts was significantly improved when 1000 µM of serine was added. Analysis of endogenous serine synthases gene expression in oocytes and embryos revealed that phosphoglycerate dehydrogenase, the rate-limiting enzyme in the serine synthesis pathway, is expressed at the morula stage and beyond. The addition of serine at 1000 µM increased the amount of methyl donors; moreover, the addition of an inhibitor of serine-metabolizing enzymes decreased the number of methyl donors and markedly inhibited blastocyst formation. These results indicate that the addition of serine at an optimal concentration of 1000 µM favors production of four-criteria-compliant blastocysts, and that methyl donor synthesis may be involved in this effect.